Peran Edukasi dan Pelatihan dalam Upaya Pencegahan Korupsi di Lingkungan Perbankan - Angelina Reski Apriliana (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Banking is crucial in efforts to prevent corruption, serving as the frontline in financial management and transactions. This article examines the role of education and training in combating corruption within the banking sector. The study aims to demonstrate that corruption in banking can undermine public trust and economic stability. I employ a literature review and observations of education and training initiatives aimed at corruption prevention in banking. Key issues identified include employees' inadequate understanding of work ethics and anti-corruption policies, along with insufficient systematic training. This research analyzes various education and training programs implemented in banks and assesses their effectiveness in enhancing employee awareness and commitment to anti-corruption practices. I highlight that comprehensive education and continuous employee training are essential for significantly mitigating the risk of corruption in banking by fostering a transparent and ethical organizational culture. It is critical for banking institutions to enhance anti-corruption awareness among their employees. Training programs should engage all employee levels and include regular evaluations to assess their effectiveness. Ultimately, the goal is to create a safer banking environment free from corrupt practices.